Non-equilibrium electron transport induced by terahertz radiation in the topological and trivial phases of Hg1−xCdxTe - Galeeva, Alexandra V.; Artamkin, Alexey I.; Kazakov, Alexey S.; Danilov, Sergey N.; Dvoretskiy, Sergey A.; Mikhailov, Nikolay N.; Ryabova, Ludmila I.; Khokhlov, Dmitry R. (Beilstein Journal of Nanotechnology, 2018)
Terahertz photoconductivity in heterostructures based on n-type Hg1−xCdxTe epitaxial films both in the topological phase (x < 0.16, inverted band structure, zero band gap) and the trivial state (x > 0.16, normal band structure) has been studied. We show that both the positive photoresponse in films with x < 0.16 and the negative photoconductivity in samples with x > 0.16 have no low-energy threshold. The observed non-threshold positive photoconductivity is discussed in terms of a qualitative model that takes into account a 3D potential well and 2D topological Dirac states coexisting in a smooth topological heterojunction.
Keywords: terahertz radiation; topological insulator; photoconductivity

(untitled) - Bernevig, B. A.; Hughes, T. A.; Zhang, S.-C. (Science, 2006)

(untitled) - König, M.; Wiedmann, S.; Brüne, C.; Roth, A.; Buhmann, H.; Molenkamp, L. W.; Qi, X.-L.; Zhang, S.-C. (Science, 2007)

(untitled) - Hasan, M. Z.; Kane, C. L. (Rev. Mod. Phys., 2010)

(untitled) - Bansil, A.; Lin, H.; Das, T. (Rev. Mod. Phys., 2016)

(untitled) - Brüne, C.; Liu, C. X.; Novik, E. G.; Hankiewicz, E. M.; Buhmann, H.; Chen, Y. L.; Qi, X. L.; Shen, Z. X.; Zhang, S. C.; Molenkamp, L. W. (Phys. Rev. Lett., 2011)

(untitled) - Crauste, O.; Ohtsubo, Y.; Ballet, P.; Delplace, P.; Carpentier, D.; Bouvier, C.; Meunier, T.; Taleb-Ibrahimi, A.; Levy, L. P. (arXiv, 2013)

(untitled) - Liu, C.; Bian, G.; Chang, T.-R.; Wang, K.; Xu, S.-Y.; Belopolski, I.; Miotkowski, I.; Cao, H.; Miyamoto, K.; Xu, C.; Matt, C. E.; Schmitt, T.; et al. (Phys. Rev. B, 2015)

(untitled) - Orlita, M.; Basko, D. M.; Zholudev, M. S.; Teppe, F.; Knap, W.; Gavrilenko, V. I.; Mikhailov, N. N.; Dvoretskii, S. A.; Neugebauer, P.; Faugeras, C.; Barra, A.-L.; Martinez, G.; et al. (Nat. Phys., 2014)

(untitled) - Valdés Aguilar, R.; Stier, A. V.; Liu, W.; Bilbro, L. S.; George, D. K.; Bansal, N.; Wu, L.; Cerne, J.; Markelz, A. G.; Oh, S.; Armitage, N. P. (Phys. Rev. Lett., 2012)

(untitled) - Wu, L.; Brahlek, M.; Valdés Aguilar, R.; Stier, A. V.; Morris, C. M.; Lubashevsky, Y.; Bilbro, L. S.; Bansal, N.; Oh, S.; Armitage, N. P. (Nat. Phys., 2013)

(untitled) - Luo, C. W.; Chen, H.-J.; Tu, C. M.; Lee, C. C.; Ku, S. A.; Tzeng, W. Y.; Yeh, T. T.; Chiang, M. C.; Wang, H. J.; Chu, W. C.; Lin, J.-Y.; Wu, K. H.; et al. (Adv. Opt. Mater., 2013)

(untitled) - Rogalski, A. (Rep. Prog. Phys., 2005)

(untitled) - Galeeva, A. V.; Artamkin, A. I.; Mikhailov, N. N.; Dvoretskii, S. A.; Danilov, S. N.; Ryabova, L. I.; Khokhlov, D. R. (JETP Lett., 2017)

(untitled) - Dvoretsky, S.; Mikhailov, N.; Sidorov, Yu.; Shvets, V.; Danilov, S.; Wittman, B.; Ganichev, S. (J. Electron. Mater., 2010)

(untitled) - Hansen, G. L.; Schmidt, J. L.; Casselman, T. N. (J. Appl. Phys., 1982)

(untitled) - Chu, J.; Xu, S.; Tang, D. (Appl. Phys. Lett., 1983)

(untitled) - Schmit, J. L.; Stelzer, E. L. (J. Appl. Phys., 1969)

(untitled) - Scott, M. W. (J. Appl. Phys., 1969)

(untitled) - Finkman, E.; Nemirovsky, Y. (J. Appl. Phys., 1979)

(untitled) - Wiley, I. D.; Dexter, R. N. (Phys. Rev., 1969)

(untitled) - Galeeva, A. V.; Egorova, S. G.; Chernichkin, V. I.; Tamm, M. E.; Yashina, L. V.; Rumyantsev, V. V.; Morozov, S. V.; Plank, H.; Danilov, S. N.; Ryabova, L. I.; Khokhlov, D. R. (Semicond. Sci. Technol., 2016)

(untitled) - Galeeva, A. V.; Krylov, I. V.; Drozdov, K. A.; Knjazev, A. F.; Kochura, A. V.; Kuzmenko, A. P.; Zakhvalinskii, V. S.; Danilov, S. N.; Ryabova, L. I.; Khokhlov, D. R. (Beilstein J. Nanotechnol., 2017)

(untitled) - Ganichev, S. D.; Ziemann, E.; Gleim, T.; Prettl, W.; Yassievich, I. N.; Perel, V. I.; Wilke, I.; Haller, E. E. (Phys. Rev. Lett., 1998)

(untitled) - Ganichev, S. D.; Yassievich, I. N.; Prettl, W.; Diener, J.; Meyer, B. K.; Benz, K. W. (Phys. Rev. Lett., 1995)

(untitled) - Ganichev, S. D.; Terent’ev, Y. V.; Yaroshetskii, I. D. (Sov. Tech. Phys. Lett., 1985)

(untitled) - Ganichev, S. D.; Yassievich, I. N.; Prettl, W. (J. Phys.: Condens. Matter, 2002)

(untitled) - Egorova, S. G.; Chernichkin, V. I.; Ryabova, L. I.; Skipetrov, E. P.; Yashina, L. V.; Danilov, S. N.; Ganichev, S. D.; Khokhlov, D. R. (Sci. Rep., 2015)

(untitled) - Rumyantsev, V. V.; Kozlov, D. V.; Morozov, S. V.; Fadeev, M. A.; Kadykov, A. M.; Teppe, F.; Varavin, V. S.; Yakushev, M. V.; Mikhailov, N. N.; Dvoretskii, S. A.; Gavrilenko, V. I. (Semicond. Sci. Technol., 2017)

(untitled) - Rumyantsev, V. V.; Morozov, S. V.; Antonov, A. V.; Zholudev, M. S.; Kudryavtsev, K. E.; Gavrilenko, V. I.; Dvoretskii, S. A.; Mikhailov, N. N. (Semicond. Sci. Technol., 2013)

(untitled) - Volkov, B. A.; Idlis, B. G.; Usmanov, M. S. (Phys.-Usp., 1995)

(untitled) - Volkov, V. A.; Enaldiev, V. V. (J. Exp. Theor. Phys., 2016)

(untitled) - Tchoumakov, S.; Jouffrey, V.; Inhofer, A.; Bocquillon, E.; Plaçais, B.; Carpentier, D.; Goerbig, M. O. (Phys. Rev. B, 2017)